Coffee Farmers' Obligations Response to 4C Certification in South OKU Regency South Sumatra Province, Indonesia - Oktarina, Yetty; Sebagustionnes, Angga; Mukhlis, Mukhlis (Agro Bali : Agricultural Journal, 2024)
The increasing demand for certified coffee has encouraged coffee exporters in Indonesia to try to help and certify coffee in their areas. Sustainable standards and certification can encourage coffee farmers to implement GAP rather than economically, socially and environmentally sustainable coffee production, the standard code coffee community (4C) certification used globally reaches 1,768,272 tons. The study aimed to determine whether farmers agreed to the implementation of 4C coffee certification in South OKU Regency. The sample was made of coffee farmers in South Ogan Komering Ulu Regency located in Pulau Beringin and Runjung Agung Districts, taken randomly and measured using a Likert scale. The study results showed that farmers agreed to implement 4C, which is in the economic, social, and environmental dimensions. Regarding environmental aspects, several important things are overlooked, especially restrictions on the use of pesticides, considering that farmers are currently accustomed to using insecticides and herbicides.